FRI0301 Prognosis of The Idiopathic Inflammatory Myopathies Associated with Interstitial Lung Disease: Preliminary Analysis of The Registry Remicam. (15th July 2016) - Cobo-Ibáñez, T.; Nuño, L.; García, M.J.; Joven, B.; Maldonado, V.; Llorente, I.; Barbadillo, C.; Garcia De La Peña, P.; Ruiz, L.; Moruno, H.; Almodόvar, R.; Lojo, L.; et al.
Abstract : Background: Some studies suggest that clinical subgroups of idiopathic inflammatory myopathies (IIM) and several myositis-specific antibodies (MSAs) could influence the prognosis of IIM with interstitial lung disease (ILD). Objectives: To investigate the prognosis value of different clinical subgroups and of MSAs in a cohort of patients with IIM -associated ILD. Methods: We analyzed patients with IIM-associated ILD included in the multicenter registry REMICAM (1980–2014). We compared prognosis between a) subgroups of IIM: dermatomyositis (DM) vs. polymiosytis (PM) (primary, juvenile, cancer-associated myositis or overlap myositis); and b) absence (−) or presence (+) of anti-Jo1 vs. anti-RO vs. anti-Jo1 and anti-RO. In this preliminary analysis, outcomes were mortality and change between final and initial visit in FVC and DLCO. Results: 478 patients were included in the registry, of which 143 had ILD, 66% PM and 34% DM. The distribution by MSAs was: 56% anti-Jo1-/RO-, 20% anti-Jo1+, 9% anti-RO+ and 15% anti-Jo1+/RO+. There were 52 deaths; the main causes were 32.6% cardiovascular events and 22.4% infections without difference between subgroups of IIM. The probability of survival was 50% to 18.8 years and the mortality rate was 37.7/1000 patient-ys. We did not find differences when we compared survival between subgroups of IIM or we compared by MSAs. FVC seemed to improve more in DM than in PM patients (1.2±5.2vs. 0.5±4.7;p=0.059), but there were no significant changes in DLCO of DM patients or in FVC and DLCO according to MSAs. Conclusions: We did not find prognostic differences in the causes of mortality, mortality rate between subgroups of IIM, or in mortality rate according to MSAs in patients with ILD. In DM patients there was a trend towards a greater improvement of FVC than in PM patients. Disclosure of Interest: None declared